A case of severe uterine arteriovenous malformation treated with danazol followed by a transarterial embolization of unilateral uterine and ovarian arteries - Hiroyuki Yazawa; Syu Soeda; Tsuyoshi Hiraiwa; Masayo Takaiwa; Keiya Fujimori (Wolters Kluwer Medknow Publications, 2015)
Uterine arteriovenous malformation (AVM) is a potentially life-threatening condition characterized by abrupt and profuse uterine bleeding from abnormal connections between arteries and veins in the myometrium. It is commonly associated with prior pregnancy or uterine trauma. We present a case of severe uterine AVM treated with danazol and transarterial embolization (TAE). A 38-year-old patient with a history of two abortions and a myomectomy was referred to our hospital for intermittent massive uterine bleeding. She was diagnosed with uterine AVM by transvaginal color Doppler ultrasonography and helical computed tomography (CT). Diagnostic three-dimensional CT (3D-CT) angiography clearly demonstrated hypervascular tangles of uterine vessels, feeding arteries, remarkably dilated draining veins, as well as early filling of the internal iliac vein and the inferior vena cava, indicating massive arteriovenous shunting in the uterus. Danazol was administrated for 10 months to reduce the shunting of the uterine AVM before TAE with N-butyl-cyanoacrylate of the left ovarian artery and left uterine artery was successfully performed. After the procedure, we confirmed that shunting through the uterine AVM was markedly reduced. The patient has not experienced any severe uterine bleeding since the treatment.